2018
DOI: 10.1016/j.jbiomech.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and kinetics of the shoe during human slips

Abstract: This paper quantified the heel kinematics and kinetics during human slips with the goal of guiding available coefficient of friction (ACOF) testing methods for footwear and flooring. These values were then compared to the testing parameters recommended for measuring shoe-floor ACOF. Kinematic and kinetic data of thirty-nine subjects who experienced a slip incident were pooled from four similar human slipping studies for this secondary analysis. Vertical ground reaction force (VGRF), center of pressure (COP), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…SLS is a reference contaminant from the ASTM F2913-17 standard (2017) and has been used in previous work (Jones et al, 2018) to simulate a detergent aqueous solution. Water is the most common low viscosity contaminant used in traction testing (A. Iraqi, Cham, Redfern, Vidic, & Beschorner, 2018; Jones et al, 2018) and is ubiquitous in work and living environments.…”
Section: Methodsmentioning
confidence: 99%
“…SLS is a reference contaminant from the ASTM F2913-17 standard (2017) and has been used in previous work (Jones et al, 2018) to simulate a detergent aqueous solution. Water is the most common low viscosity contaminant used in traction testing (A. Iraqi, Cham, Redfern, Vidic, & Beschorner, 2018; Jones et al, 2018) and is ubiquitous in work and living environments.…”
Section: Methodsmentioning
confidence: 99%
“…The geometric design of footwear has been shown to affect human balance and gait [ 12 , 14 , 15 , 16 , 17 ]. Few studies have focused on their impact on the use of alternative footwear such as the thong-styled flip flops and open-toed sandals on the biomechanics of human gait [ 18 , 19 , 21 , 28 , 29 ] and how the footwear affects the severity of slip related events [ 4 , 22 , 23 , 30 ]. Footwear serves as the interface between the human body and the supporting surface and can affect human balance and gait adversely [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has raised questions whether these testing conditions reflect the under-heel conditions during slipping. For example, studies on unexpected slips have determined that the shoe angle is between 15 and 24° at the moment that the foot starts to slip, which is greater than the 7° used in these testing methods (Albert et al 2017, Iraqi et al 2018b. Furthermore, the normal forces at slip initiation are typically less than 300 N but then achieve approximately 500 N during the peak slipping speed (Iraqi et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies on unexpected slips have determined that the shoe angle is between 15 and 24° at the moment that the foot starts to slip, which is greater than the 7° used in these testing methods (Albert et al 2017, Iraqi et al 2018b. Furthermore, the normal forces at slip initiation are typically less than 300 N but then achieve approximately 500 N during the peak slipping speed (Iraqi et al 2018b). While these previous studies indicate deviations between testing conditions and slipping biomechanics at slip-start, it should be noted that the under-heel conditions vary over time and that lower shoe angles (Albert et al 2017) and higher normal forces (Iraqi et al 2018b) are observed at peak sliding speed, similar to those commonly used by the STM 603 device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation